Growth Rate in CD Ratio of Banks in Belgaum District a Diagnostic Study: Analyzing the CD Ratio and Growth Rate of Banks in Belgaum District (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Performance of banking industry is greatly depends on the CD ratio, which is the key indicator to show how the funds were utilized by the banks to generate their revenue and increase the market share. In this paper an attempt has been made to ascertain CD ratio and growth rate in CD ratio by selecting different groups of banking such as Nationalized Banks, Private Sector Banks, Regional Rural Banks (KVG) ,Belgaum District Co-Op Banks, KSCARD Banks, Urban Co-Op Banks. Analysis of deposit and advances per branch of each group reveals that as compare to nationalized banks and private banks CD ratio of other banking group shows satisfactory result over the study period.